Molecular Relationship between Strains of M. bovis from Mexico and Those from Countries with Free Trade of Cattle with Mexico. - Feliciano Milian-Suazo; Leticia Garcia-Casanova; Suelee Robbe-Austerman; Germinal Jorge Canto-Alarcon; Isabel Barcenas-Reyes; Tod Stuber; Elba Rodriguez-Hernandez; Susana Flores-Villalva (PLoS ONE, 2016)
The purpose of this study was to identify relationships between spoligotypes of M. bovis from cattle in Mexico and those reported in countries with free trade of cattle with Mexico: Australia, Canada, New Zealand and the United States of America. Mexican spoligotypes were obtained from isolates collected from cattle in different parts of the country. Spoligotypes from Canada and New Zealand were obtained from different reports in the literature. Those from the United States were obtained from the database of the National Veterinary Services Laboratory in APHIS-USDA. In order to perform the analysis in a single data set, spoligotypes were all converted to binary data and classified according to www.mbovis.org or www.pasteur-guadeloupe.fr:8081. Epidemiologic information included country and species infected. From 3,198 isolates, 174 different spoligotypes were obtained, 95 were orphans. Ninety one percent of the isolates came from the Unites States (n = 1,609) and Mexico (n = 1,323). Spoligotype SB0265 is shared between Canada and the United States in cattle and wildlife. Six spoligotypes, SB0673, SB0121, SB0145, SB0971, SB0140 and SB1165, were frequent in cattle and wildlife in the United States and cattle in Mexico, suggesting wide exchange of strains. Spoligotype SB0669 was found only in Mexico. Spoligotype SB0140 was the most common in Australia and the sixth in the United States and Mexico. In a phylogenetic analysis, spoligotype SB0140 appears as the oldest spoligotype in the data set, suggesting this as the ancestral spoligotype for all spoligotypes in the five countries. Some spoligotypes are shared by animals and humans, corroborating the zoonotic importance of M. bovis.